Chillin’ Effects of Fake News: Changes in Practices Related to Accountability and Transparency in American Newsrooms Under the Influence of Misinformation and Accusations Against the News Media - Vu, Hong Tien and Saldaña, Magdalena (Journalism & Mass Communication Quarterly, 2021)
This study examines how newsroom work in the United States has changed in response to some of the latest developments in the news media environment. Using nationally representative survey data, we explore what professional routines American journalists have adopted to avoid spreading or being accused of publishing misinformation. Findings suggest that journalists have added new or intensified practices to increase accountability and transparency. In addition, role conceptions, perception of fake news, and responsibility for social media audiences impact the adoption of such practices. Journalists are more likely to embrace transparency than accountability, suggesting the emergence of new journalistic norms in today’s newsrooms.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDc3Njk5MDIwOTg0Nzgx